ENHANCING THERMAL EFFICIENCY: STRATEGIES FOR UTILIZING HEAT CONDUCTIVITY IN COATING TECHNOLOGY - Gulnoza Jalilova (European Science Publishing, 2024)
This article covers the methods currently used to determine the thermal conductivity of these heat-insulating coatings as well as the results of experimental research on the development and analysis of energy-efficient materials and how they are applied to newly constructed modern buildings and structures.
Keywords: Microsphere, heat-insulating paint, thermal conductivity, energy efficiency, and thermocouple sensors.